Evidential limitations in separate proceedings in commercial cases (Discourse of Law and Administration, 2021)
The introduction of separate proceedings in commercial cases into the civil contentious procedure gives rise to numerous doubts, including restrictive evidential limitations. The obligation imposed on the parties to prove each activity by means of a document may in many cases prove difficult to implement. Doubts are also raised by the scope of admissibility and the order in which evidence is taken from the testimony of witnesses and the parties to be heard. Finally, the exclusion of specific evidence may result from the evidence agreement concluded by the parties. These restrictions may, paradoxically, make it difficult for the court to hear and adjudicate a commercial case quickly.
Keywords: commercial cases; document; evidence agreement